Encyclopedia of Terminology for Educational Communications and Technology
XXXII, 338 p.
Keywords: The words that describe the educational technology field span a wide array of specializations and theoretical orientations. To further complicate this state of affairs, the vocabulary of the field is constantly changing: new words emerge and the definitions of existing words change to reflect particular nuances of thought, technological advancements, or even the disparate global interpretations of a given term. The Encyclopedia of Terminology for Educational Communications and Technology is written to address these issues. Written for both scholars and practitioners, this is a volume of scholarly definitions and short discussions of approximately 180 key terms of the field. Each entry includes material such as the salient attributes of the term, any alternative views and interpretations of the term, and future trends. The definition discussions are supported with relevant literature from educational communications and technology and related fields, such as communications or educational psychology. Individual signed entries are written by over 50 established scholars from throughout the field and throughout the world. A definitive compilation of key terms in the field of Educational Technology assembled in one place, the Encyclopedia of Terminology for Educational Communications and Technology ill prove an indispensible reference for scholars, researchers and practitioners alike. .